Interannual variation in effective number of breeders and estimation of effective population size in long‐lived iteroparous lake sturgeon ( Acipenser fulvescens ) - Thuy Yen Duong; Kim T. Scribner; Patrick S. Forsythe; James A. Crossman; Edward A. Baker (Molecular Ecology, 2013)
Quantifying interannual variation in effective adult breeding number ( N b ) and relationships between N b , effective population size ( N e ), adult census size ( N ) and population demographic characteristics are important to predict genetic changes in populations of conservation concern. Such relationships are rarely available for long‐lived iteroparous species like lake sturgeon ( Acipenser fulvescens ). We estimated annual N b and generational N e using genotypes from 12 microsatellite loci for lake sturgeon adults ( n = 796) captured during ten spawning seasons and offspring ( n = 3925) collected during larval dispersal in a closed population over 8 years. Inbreeding and variance N b estimated using mean and variance in individual reproductive success derived from genetically identified parentage and using linkage disequilibrium ( LD ) were similar within and among years (interannual range of N b across estimators: 41–205). Variance in reproductive success and unequal sex ratios reduced N b relative to N on average 36.8% and 16.3%, respectively. Interannual variation in N b /N ratios (0.27–0.86) resulted from stable N and low standardized variance in reproductive success due to high proportions of adults breeding and the species' polygamous mating system, despite a 40‐fold difference in annual larval production across years (437–16 417). Results indicated environmental conditions and features of the species' reproductive ecology interact to affect demographic parameters and N b /N . Estimates of N e based on three single‐sample estimators, including LD , approximate Bayesian computation and sibship assignment, were similar to annual estimates of N b . Findings have important implications concerning applications of genetic monitoring in conservation planning for lake sturgeon and other species with similar life histories and mating systems.